Pendampingan Peningkatan Pengetahuan dan Keahlian Petani dalam Mengoptimalkan Produksi Nenas Melalui Pemasaran dan Analisis Harga Produk - Mayla Khoiriyah; Ulfa Afifah; Raja Adri Satriwan; Arumega Zarefar; Atika Zarefar; Vera Oktari; Ruhul Fitrios (Politeknik Caltex Riau, 2024)
This activity is carried out in the form of assistance so that the community's knowledge and expertise increase so that the community's pineapple production can be optimized through marketing and product price analysis. The service was carried out in Kualu Nenas Village, Kampar Regency. This is due to the ineffectiveness of marketing channels and the lack of knowledge and expertise of farmers in running effective and efficient pineapple derivative product business. This service is expected to contribute to increasing the productivity of pineapple farmers in Kualu Nenas Village, so that it can improve standard of living of the community. The output of this activity is a scientific articles and mass media publications.